2019
DOI: 10.1590/s0100-83582019370100025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Density and Development Stage of Ryegrass on Glyphosate Effectiveness

Abstract: Glyphosate is one of the main herbicides used to control ryegrass. The objective of this research was to evaluated whether the glyphosate dose-response curve is affected by density of ryegrass plants in two phenological growth stages. To attend this objective, two experiments were carried out in greenhouse (one with Lolium multiflorum and another with Lolium rigidum) and two under field conditions. In the greenhouse experiments, the experimental design was a completely randomized design in a factorial scheme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The use of residual herbicides reduced the initial LOLMU and URPLA densities favoring their control in post-emergence. In a recent article, the authors concluded that it is more challenging to control GR LOLMU in high densities and that to reach the same level of control as those obtained with low weed density is necessary to increase the herbicide dose (Fipke and Vidal 2019). However, the results of the present study indicate that the application of atrazine + S-metolachlor in corn pre-emergence is a more efficient alternative than increasing the glyphosate rate or even the number of applications in postemergence.…”
Section: Effects Of Post-emergence Herbicides On Lolmu and Urpla Densitiesmentioning
confidence: 49%
See 1 more Smart Citation
“…The use of residual herbicides reduced the initial LOLMU and URPLA densities favoring their control in post-emergence. In a recent article, the authors concluded that it is more challenging to control GR LOLMU in high densities and that to reach the same level of control as those obtained with low weed density is necessary to increase the herbicide dose (Fipke and Vidal 2019). However, the results of the present study indicate that the application of atrazine + S-metolachlor in corn pre-emergence is a more efficient alternative than increasing the glyphosate rate or even the number of applications in postemergence.…”
Section: Effects Of Post-emergence Herbicides On Lolmu and Urpla Densitiesmentioning
confidence: 49%
“…High density and not adequate stage of GR LOLMU are two factors that make it difficult to control with a burndown application before corn establishment. The poorly controlled plants will likely interfere with corn development and can reduce the crop yield up to 48% (Nandula 2014;Fipke and Vidal 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent study, Trezzi et al [46] reported that the retention rate significantly impacts the efficiency of imazamox, which supports our results. However, it should be kept in mind that the effectiveness of herbicides is significantly affected by the weed development stage and density; if the stages increase further, the weeds become more tolerant and the efficacy of the herbicides decreases [47]. Therefore, the application time is crucial for reaching satisfactory control with the lowest herbicide doses.…”
Section: Discussionmentioning
confidence: 99%